Long non‐coding RNA TCONS_00041960 enhances osteogenesis and inhibits adipogenesis of rat bone marrow mesenchymal stem cell by targeting miR‐204‐5p and miR‐125a‐3p. Issue 8 (28th February 2018) - Shang, Guowei; Wang, Yadong; Xu, Yan; Zhang, Shanfeng; Sun, Xiaoya; Guan, Hongya; Zhao, Xuefeng; Wang, Yisheng; Li, Yuebai; Zhao, Guoqiang
Abstract : A growing number of long non‐coding RNAs (lncRNAs) have been found to be involved in diverse biological processes such as cell cycle regulation, embryonic development, and cell differentiation. However, limited knowledge is available concerning the underlying mechanisms of lncRNA functions. In this study, we found down‐regulation of TCONS_00041960 during adipogenic and osteogenic differentiation of glucocorticoid‐treated bone marrow mesenchymal stem cells (BMSCs). Furthermore, up‐regulation of TCONS_00041960 promoted expression of osteogenic genes Runx2, osterix, and osteocalcin, and anti‐adipogenic gene glucocorticoid‐induced leucine zipper (GILZ). Conversely, expression of adipocyte‐specific markers was decreased in the presence of over‐expressed TCONS_00041960. Mechanistically, we determined that TCONS_00041960 as a competing endogenous RNA interacted with miR‐204‐5p and miR‐125a‐3p to regulate Runx2 and GILZ, respectively. Overall, we identified a new TCONS_00041960‐miR‐204‐5p/miR‐125a‐3p‐Runx2/GILZ axis involved in regulation of adipogenic and osteogenic differentiation of glucocorticoid‐treated BMSCs. Abstract : In this study, we elucidated that LncRNA TCONS_00041960 as a competing endogenous RNA interacted with miR‐204‐5p and miR‐125a‐3p to regulate Runx2 and GILZ, respectively. Moreover, we identified a new TCONS_00041960‐miR‐204‐5p/miR‐125a‐3p‐Runx2/GILZ axis involved in regulation of adipogenic and osteogenic differentiation of glucocorticoid‐treated BMSCs.